I prefissi verbali nella Povest' vremennych let Per un'analisi del processo di formazione dell'aspetto verbale in russo - RUVOLETTO, LUISA (Biblioteca di Studi Slavistici, 2016)
Through the analysis of the predetermined verbal forms of the Povest 'vremennych let (11th-12th centuries), this book sheds light on the aspectual meanings of verbs with prefix, in order to verify the degree of evolution of the Slavic-oriental aspectual system in the most ancient phase of its attestation. The study on prefixes and the ways in which they interact with the actional characteristics of the starting verbs allows us to identify the consequences of prefixing at the lexical, actional and aspectual level. Terminative verbs with prefix acquire the resultative value ("protoperfective") and are subjected, in part, to secondary suffixation, a phenomenon that will contribute to the grammaticalization of the aspectual category in Russian and other Slavic languages.